Pemuda Cerdas Digital: Pelatihan Desain Grafis dengan Canva di SMA Imelda Medan - Sari, Ika Yusnita; Rahmi, Elvika; Khairunnisa, Khairunnisa; Lumbanbantu, Maristella J; Marpaung, Astrida N (CV. Devi Tara Innovations, 2024)
The program titled